Terrorism and the internet: How dangerous is online radicalization? - Binder, Jens F.; Kenyon, Jonathan (Frontiers in Psychology, 2022)
This work is concerned with the extent and magnitude of threat related to online radicalization in the context of terrorist acts and related offending. Online influences have been depicted as major drivers for the propagation and adoption of extremist ideologies, which often contain an element of collective grievance, and subsequent acts of violence. This is most pronounced in the discussion of so-called lone actor terrorism, but extends to all forms of extremist offending, and beyond. The present work situates online radicalization leading to terrorist acts within the wider context of grievance-based beliefs and attitudes. Further, it addresses current positions and debates surrounding the relevance and mechanisms of online radicalization in terrorist offending. Recent evidence from quantitative studies is reviewed to estimate prevalence of online radicalization and the level of threat that results from it. This is followed by a discussion of plausible, but opposing, interpretations of the estimates presented. While online radicalization does occur, with and without reference to offline processes, the resulting threat is not overly high. This assessment, however, refers to the present only and is unlikely to hold for the future, given the general growth and acceleration of online activity among terrorist actors.